2023
DOI: 10.1007/s12134-023-01024-w
|View full text |Cite
|
Sign up to set email alerts
|

Differential Probability in Unmet Healthcare Needs Among Migrants in Four European Countries

Abstract: Migrants and refugees try to reach Europe to seek protection and a better life. The responsiveness and stewardship of the European countries health system have an impact on the ability to access healthcare. This study aims to investigate the differential probability of healthcare unmet needs among migrants living in four European countries. We used a 2019 cross-sectional data from the European Union Income and Living Conditions survey. We performed a two-stage probit model with sample selection, first to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“… 13 For example, a cross sectional study using 2019 data from the European Union Income and Living Conditions survey shows that migrants have higher unmet healthcare needs than non-migrants. 14 …”
Section: Deficiencies Of Current Uhc Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“… 13 For example, a cross sectional study using 2019 data from the European Union Income and Living Conditions survey shows that migrants have higher unmet healthcare needs than non-migrants. 14 …”
Section: Deficiencies Of Current Uhc Measuresmentioning
confidence: 99%
“…13 For example, a cross sectional study using 2019 data from the European Union Income and Living Conditions survey shows that migrants have higher unmet healthcare needs than non-migrants. 14 In many countries, over half of older adults have chronic conditions and disabilities that health systems are poorly equipped to manage, giving rise to unmet need. 15 A WHO Kobe Centre analysis of survey data in 2021-22 from 83 countries showed that the prevalence of self-reported unmet healthcare needs of adults aged 60-69 tends to be lower in countries with higher SCI values, but outliers like the US have both high SCI and high unmet need.…”
Section: Deficiencies Of Current Uhc Measuresmentioning
confidence: 99%